The effect of thoracolumbosacral orthosis on scoliosis progression and chest deformity in children with type 1 spinal muscular atrophy: A randomized controlled trial - Emre Dansuk; Ayşe Nur Tunalı Van Den Berg; Görkem Ata; Seval Kutluturk Yıkılmaz; Sedat Oktem (PLoS ONE, 2025)
Background Type 1 spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disease characterized by severe muscle weakness, which results in progressive spinal and chest deformities. This study aims to evaluate the effect of thoracolumbosacral orthosis (TLSO) use along with pulmonary care (PC), individualized pulmonary rehabilitation (IPR), and individualized trunk exercises (ITE) in children with Type 1 SMA. Methods The study enrolled 24 children with Type 1 SMA aged 2–6 years, with a scoliosis angle of 20°–40°. Participants were randomly assigned into two groups using a stratified randomization method: Group 1 (PC, IPR, ITE) and Group 2 (PC, IPR, ITE & TLSO). All participants underwent an 8-week treatment program. Pre- and post-treatment assessments included scoliosis progression measured by the Cobb angle, chest deformity evaluated through the basal upper-lower chest wall ratio and the Supine Angle of Trunk Rotation Test (SATR), and motor function levels assessed using the Children’s Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND). Results Significant improvements were observed in Cobb angle, bell-shaped chest deformity, and motor function in both groups (p < 0.05). Group 2 demonstrated greater improvements in effect size (ES) across all evaluation parameters. Compared to Group 1, Group 2 showed superior improvement in Cobb angle (ES = 3.98), basal upper-lower chest wall ratio (ES = 5.00), SATRL (lower) (ES = 2.55), SATRU (upper) (ES = 1.64), and CHOP INTEND (ES = 1.23) (p < 0.05). Conclusions This study is the first to demonstrate that the combination of PC, IPR, ITE, and TLSO yields superior clinical outcomes in children with Type 1 SMA. The findings support current recommendations for TLSO use in patients with a Cobb angle >20°, and emphasize the potential benefits of early, proactive orthotic intervention when integrated with mobilization, trunk, and pulmonary exercise programs in managing scoliosis in this population. However, limitations such as the small sample size and short follow-up period underscore the need for larger and longer-term studies to confirm these findings. Trial Registiration: NCT05878418